Impact of SARS-CoV-2 virus pandemic on the future of cadaveric dissection anatomical teaching - Ooi, Setthasorn Zhi Yang (Med Educ Online, 2020)
The SARS-CoV-2 virus pandemic has left a huge impact on medical education globally. An area that has not been discussed in medical education is the potential implications of the cessation of body and organ donations on medical education. We explore the implications of this on the future of cadaveric dissections in anatomy teaching amidst the SARS-CoV-2 virus pandemic.